Stakeholder insights into implementing a systems-based suicide prevention program in regional and rural tasmanian communities - Laura Grattidge; Terry Purton; Stuart Auckland; David Lees; Jonathan Mond (BMC, 2022)
Abstract Purpose With emerging evidence indicating that systems-based approaches help optimise suicide prevention efforts, the National Suicide Prevention Trial sought to gather evidence on the appropriateness of these approaches to prevent suicide among at-risk populations, in regional and rural communities throughout Australia. The Tasmanian component of the Trial implemented the LifeSpan systems framework across three distinct rural areas with priority populations of men aged 40-64 and people 65 and over. The University of Tasmania's Centre for Rural Health undertook a local-level evaluation of the Trial. Aims To explore key stakeholder perceptions of implementing a systems-based suicide prevention program in regional and rural communities in Tasmania, Australia. Method This study utilised qualitative methods to explore in depth, stakeholder perspectives. Focus groups and interviews were conducted with 46 participants, comprising Trial Site Working Group members (n = 25), Tasmania's Primary Health Network employees (n = 7), and other key stakeholders (n = 14). Approximately half of participants had a lived experience of suicide. Data were thematically analysed using NVivo. Results Key themes centred on factors impacting implementation of the Trial. These included how the Trial was established in Tasmania; Working Group governance structures and processes; communication and engagement processes; reaching priority population groups; the LifeSpan model and activity development; and the effectiveness, reach and sustainability of activities. Discussion Communities were acutely aware of the need to address suicide in their communities, with the Trial providing resources and coordination needed for community engagement and action. Strict adherence to the Lifespan model was challenging at the community level, with planning and time needed to focus on strategies influencing whole or multiple systems, for example health system changes, means restriction. Perceived limitations around implementation concerned varied community buy-in and stakeholder engagement and involvement, with lack of role clarity cited as a barrier to implementation within Working Groups. Barriers delivering activities to priority population groups centred around socio-cultural and technological factors, literacy, and levels of public awareness. Working Groups preferred activities which build on available capital and resources and which meet the perceived needs within the whole community. Approaches sought to increase awareness of suicide and its prevention, relationships and partnerships, and the lived experience capacity in Working Groups and communities. Conclusion Stakeholder insights of implementing the National Suicide Prevention Trial in regional and rural Tasmanian from this study can help guide future community-based suicide prevention efforts, in similar geographic areas and with high-risk groups.